Stepping Lively in Place : The Not-Married, Free Women of Civil-War-Era Natchez, Mississippi - Broussard, Joyce Linda (Book collections on Project MUSE., 2016)
"Enlivened with profiles and vignettes of some of the remarkable people whose histories inform this study, Stepping Lively in Place shows how single, free women navigated life in a busy slave-encrusted river-port town before, during, and after the Civil War. It examines how single women in one city (including prostitutes, entre-preneurs, and elite plantation ladies) coped with life unencumbered, or unprotected, by husbands. The book pays close attention to the laws affecting Southern gender and sociocultural traditions, focusing especially on how the town's single women maneuvered adroitly but guardedly within the legal arena in which they lived. Joyce Linda Broussard looks at all types of single women--black and white, law-abiding and criminal--including spinsters, widows, divorcees, and abandoned women. She demonstrates the nuanced degrees to which these women understood that the legal, cultural, and social traditions of their place and time could alternately constrain or empower them, often achieving thereby a considerable amount of independence as women"--Provided by publisher.